Design, model and analysis of a hybrid multi renewable energy small scale power system for jetties - Yuya Lainmar Toe Kyaw Sunn (2014)
Due to the nature of the finite world, the extent of fossil fuels that could be extracted is dwindling day by day. Renewable energy is a popular alternative to the traditional way of generating electricity and starting to become mature over the years. This report presents the details of the development of a hybrid multi renewable energy small-scale power system that includes a photovoltaic array, wind turbine and wave energy converter as the main sources of power. The modelling of the system took place entirely in the MATLAB/Simulink environment. This report will discuss details of the design and development of the photovoltaic array as well as the wind turbine generator. Components that are part of the system such as rectifier, inverter, filter, transformer and voltage regulator would also be discussed in detail as well. There is also a dedicated chapter to present an operational analysis of the developed hybrid system. Future improvements that could be made to the system are also available in the final chapter.